Hak Milik Atas Tanah Adat Di Wilayah Kepulauan - Mispa Christian Science Paisina; Adonia Ivone Laturette; Novyta Uktolseja (PAMALI: Pattimura Magister Law Review, 2021)
Introductioan: The Western Seram Islands have various customary rights that grow and develop in the lives of indigenous peoples and it becomes a rule that is believed by them, so that it becomes a law that binds them in determining their ownership rights to their customary land.Purposes of the Research: This study aims to determine how the position of customary land ownership rights in the national land law system, and what is the legal basis and the way in which customary land ownership rights occur according to customary law.Methods of the Research: This study uses the normative legal research method, which aims to find out how the position of ownership rights over customary land in the national land law system in the areas of Taniwel Timur, Negeri Maloang and Negeri Sohuwe, West Seram Regency, Maluku Province, and to understand what the legal basis and How to Have Land Ownership Rights According to Customary Law in the Taniwel Timur District, Maloang State and Sohuwe State, West Seram Regency, Maluku Province.Results of the Research: In principle, ownership of land rights by a member or group of customary law communities, whether individual or communal / group, has a very binding power de jure and de facto. The principle of ownership in the provision of de jure guarantees in the sense that the customary law community recognizes that if ownership rights are obtained by means of the permission of the head of the association (Kepala Adat or Kepala Soa), to open and manage land for customary law communities it can be said to be a legal act that is legal according to law. adat as long as it does not contradict the prevailing customary law norms, and the principle of ownership in a de facto manner, namely that the principle of ownership has been obtained from generation to generation. This is what the local government must pay attention to in terms of recognition of rights by customary law communities in West Seram District, Maluku Province.